2017
DOI: 10.1111/apa.13829
|View full text |Cite
|
Sign up to set email alerts
|

Higher growth, fat and fat‐free masses correlate with larger cerebellar volumes in preterm infants at term

Abstract: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
3
29
2
Order By: Relevance
“…The positive association between lipid intake and brain volumes at 4 weeks of age seen in our study are consistent with the findings of Coviello et al, who demonstrated a significant positive association between cumulative lipid intake in the first 28 days of life and cerebellar, basal ganglia and thalamic volumes 15 . In contrast to these positive findings, studies of average macronutrient intake in preterm infants did not find a significant relationship between lipid intake and total or regional brain volumes at term‐equivalent age 39,40 . This discrepancy between average vs cumulative lipid intake in relation to brain growth warrants further investigation as we continue to explore the ideal lipid intake for optimal brain growth in the preterm population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The positive association between lipid intake and brain volumes at 4 weeks of age seen in our study are consistent with the findings of Coviello et al, who demonstrated a significant positive association between cumulative lipid intake in the first 28 days of life and cerebellar, basal ganglia and thalamic volumes 15 . In contrast to these positive findings, studies of average macronutrient intake in preterm infants did not find a significant relationship between lipid intake and total or regional brain volumes at term‐equivalent age 39,40 . This discrepancy between average vs cumulative lipid intake in relation to brain growth warrants further investigation as we continue to explore the ideal lipid intake for optimal brain growth in the preterm population.…”
Section: Discussionsupporting
confidence: 91%
“…15 In contrast to these positive findings, studies of average macronutrient intake in preterm infants did not find a significant relationship between lipid intake and total or regional brain volumes at term-equivalent age. 39,40 This discrepancy between average vs cumulative lipid intake in relation to brain growth warrants further investigation as we continue to explore the ideal lipid intake for optimal brain growth in the preterm population. The positive relationship between lipid intake and cerebellar growth is of extreme interest, as the cerebellum is the most rapidly growing brain structure during the second half of pregnancy, with healthy fetuses experiencing a remarkable 34-fold increase in cerebellar volume that far exceeds the growth of the cerebrum during this time period.…”
Section: Discussionmentioning
confidence: 99%
“…while Paviotti et al demonstrated that both fat mass and fat-free mass are related to cerebellar volume at term [7]. Further, consistent with the developmental origin of health and disease (DOHaD) concept, early life body composition is correlated with cardiovascular and metabolic diseases in adulthood [8,9].…”
Section: Introductionmentioning
confidence: 88%
“…The relationship illustrated in Figure of %fat mass and the deviation between predicted and target weight support the validity of the GVA. In contrast to the results achieved by the 2 other approaches, the GVA provides reasonable values of average %fat mass at the target weight, based on what has been shown in literature to correspond to appropriate neurodevelopment . Further, it was shown that the data points are centered and evenly distributed (similar proportion of infants with low and high %fat mass) around ΔW = 0.…”
Section: Discussionmentioning
confidence: 58%